1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

022-62211530

Mon to Sat - 11 AM to 8 PM

# prove that:

Asked by MANDAKRANTA CHAKRABORTY 26th December 2011, 10:19 AM
LHS = cos7A - cos5A - 3cos3A + 3cosA

= -2sin[(7A-5A)/2]sin[(7A+5A)/2] +3x2sin[(3A-A)/2]sin[(3A+A)/2]

= -2sinAsin6A+6sinAsin2A

= -2sinA[2sin3Acos3A] + 6sinA[2sinAcosA]

= -4sinAsin3Acos3A + 12sin2AcosA

= -4sinA[3sinA-4sin3A][4cos3A-3cosA] + 12sin2AcosA

= -4sinA[12sinAcos3A-9sinAcosA-16sin3Acos3A+12sin3AcosA] + 12sin2AcosA

= -4sinA[12sinAcosA(cos2A+sin2A)-9sinAcosA-16sin3Acos3A] + 12sin2AcosA

=  -4sinA[12sinAcosA(cos2A+sin2A)-9sinAcosA-16sin3Acos3A] + 12sin2AcosA

= -4sinA[12sinAcosA-9sinAcosA-16sin3Acos3A] + 12sin2AcosA

= -4sinA[3sinAcosA-16sin3Acos3A] + 12sin2AcosA

= -12sin2AcosA +64sin4Acos3A + 12sin2AcosA

=  64sin4Acos3A

= RHS
Answered by Expert 26th December 2011, 4:14 PM
• 1
• 2
• 3
• 4
• 5
• 6
• 7
• 8
• 9
• 10

You have rated this answer /10